Increasing biogas yield in biogas plants by adding whey to cattle manure - Witaszek, K.; Shvorov, S.; Opryshko, O.; Dudnyk, A.; Sydorovych, K.; Yakushov, V. (Energy and Automation, 2025)
Currently, the problem of replacing natural gas with biomethane based on the widespread use of biogas plants, which will ensure the production of biogas, heat, electricity and high-quality fertilizers by anaerobic digestion of organic waste, is acute. One of the directions of increasing biogas yield is the intensification of fermentation of livestock waste. The aim of the article is to increase biogas yield in biogas plants by adding whey to cattle manure. To achieve this goal, the following tasks were solved: the biogas yield was experimentally determined when cattle manure was periodically loaded into the methane tank with the addition of whey; based on the experimental data obtained, the unimodality interval for the maximum biogas yield was found in the quasi-continuous mode of loading the methane tank. The process of methanogenesis of cattle manure with the addition of whey in laboratory mini-reactors of biogas plants of the Poznań University of Life Sciences was considered. Using the dichotomy method, the optimal volumes of whey addition to the substrate were substantiated, which ensure the maximum increase in biogas (biomethane) yield.Key words: mini-reactors, biogas plants, methanogenesis research, cattle manure, whey